Retrospective identification of the first cord blood–transplanted severe aplastic anemia in a STAT1-associated chronic mucocutaneous candidiasis family: case report, review of literature and pathophysiologic background - Fink, Franz-Martin; Höpfl, Reinhard; Witsch-Baumgartner, Martina; Kropshofer, Gabriele; Martin, Sabine; Fink, Valentin; Heeg, Maximilian; Peters, Christina; Zschocke, Johannes; Haas, Oskar A. (Frontiers in Immunology, 2024)
Severe aplastic anemia (SAA) is a life-threatening bone marrow failure syndrome whose development can be triggered by environmental, autoimmune and/or genetic factors. The latter comprise germ line pathogenic variants in genes that bring about habitually predisposing syndromes as well as immune deficiencies that do so only occasionally. One of these disorders is the autosomal dominant form of chronic mucocutaneous candidiasis (CMC), which is defined by germ line STAT1 gain of function (GOF) pathogenic variants. The resultant overexpression and constitutive activation of STAT1 dysregulate the JAK/STAT signaling pathway, which normally organizes the development and proper interaction of different components of the immunologic and hematopoietic system.Although SAA is an extremely rare complication in this disorder, it gained a more wide-spread interest when it became clear that the underlying causative pathomechanism may, in a similar fashion, also be instrumental in at least some of the idiopathic SAA cases. Based on these premises, we present herein what is the historically most likely first cord-blood transplanted SAA case in a CMC family with a documented STAT1 GOF pathogenic variant. In addition, we recapitulate the characteristics of the six CMC SAA cases that have been reported so far and discuss the significance of STAT1 GOF pathogenic variants and other STAT1 signaling derangements in the context of these specific types of bone marrow failure syndromes. Since a constitutively activated STAT1 signaling, be it driven by STAT1 GOF germ line pathogenic variants or any other pathogenic variantindependent events, is apparently important for initiating and maintaining the SAA disease process, we propose to acknowledge that SAA is one of the definite disease manifestations in STAT1-mutated CMC cases. For the same reason we deem it necessary to also incorporate molecular and functional analyses of STAT1 into the diagnostic work-up of SAA cases.